Evaluation of the sedative activity of the hydroalcoholic extract from native Peruvian medicinal plants in albino mice - Palomino Huarcaya , Roger Alberto (2025)
Objective: This study evaluated the sedative effect of the hydroalcoholic extracts from the leaves of Valeriana pinnatifida Ruiz & Pav (valerian) and Passiflora edulis Sims (passionflower) in albino mice (Holtzman). Material and Methods: 30 Holtzman albino mice were used, acquired from the National Agrarian University La Molina (UNALM). The mice were selected and assigned to groups using simple random probability sampling, forming 6 groups of 5 specimens each. Each group received a different treatment with the hydroalcoholic extracts: Valeriana pinnatifida at doses of 20 mg/kg and 50 mg/kg, and Passiflora edulis at doses of 50 mg/kg and 100 mg/kg. To induce anxiety, the elevated plus maze test was used. Subsequently, ANOVA and Tukey tests were applied to determine the concentration and group with the highest sedative activity. Results: The results indicate that the hydroalcoholic extract of Valeriana pinnatifida leaves shows significant sedative activity. However, the extract of Passiflora edulis at a dose of 50 mg/kg exhibited very limited sedative activity, suggesting that its effect is less pronounced compared to valerian. In contrast, the 100 mg/kg dose of Passiflora edulis did show a notable sedative effect. Conclusions: The findings suggest that treatments based on hydroalcoholic extracts of Valeriana pinnatifida could be considered an effective therapeutic alternative for managing anxiety. On the other hand, the use of Passiflora edulis at a concentration of 50 mg/kg is not recommended as an effective sedative; however, the 100 mg/kg concentration does exhibit sedative effects. These results pave the way for future research on dose optimization and potential combinations of extracts to enhance sedative effectiveness.